KETERKAITAN ANTARA MOTIVASI, KEPERCAYAAN, NORMA SUBYEKTIF, SIKAP TERHADAP NIAT UNTUK BERBAGI PENGETAHUAN - Yustina, Tantri (Jurnal Manajemen Dayasaing, 2016)
The purpose of this study is to examine and analyze the effect of extrinsic motivation,intrinsic motivation, subjective norms, trust, and attitudes toward intention for sharingknowledge. Type of the research in this study is a quantitative reserch, by taking samples200 respondents at SMP Muhammadiyah and MTs Muhammadiyah at Sukoharjo. Thetechnique of collecting data uses questionnaires, and tested uses structural equationmodel/Structural Equation Modelling (SEM). The results of this study show that extrinsicmotivation and intrinsic motivation has no effect on the intention to share knowledge,extrinsic motivation and intrinsic motivation effect on attitudes and trust, trust andsubjective norms effect on attitudes and attitudes, and subjective norms effect on theintention for sharing knowledge.